ANTESEDEN DAN KONSEKUENSI DARI PRICE SATISFACTION - Steven Dharma; Asep Hermawan (Jurnal Manajemen dan Pemasaran Jasa, 2012)
The purpose of this paper is to explore the antecedents and consequents of price satisfaction. It argues that price satisfaction is composed of several dimensions (price transparency, pricequality ratio, relative price, price confidence, price reliability, and price fairness) and that companies should consider these dimensions when monitoring customer price satisfaction.Based on a theoretical discussion of the price dimensions, a questionnaire is developed that measures customer satisfaction with individual price dimensions. Using structural equation model analysis, the impact of price satisfaction dimensions on overall price satisfaction is measured, using a sample of 100 respondent that also customers from several car workshops.The research was analyzed with Structural Equation Model to analyze the path effect between the variable to answer the hypothesis testing. Before doing the structural equation model, thedata was tested with instrument testing, consist of validity and reliability test. Goodness fit measure was also used to make sure that the structural equation model in good fit condition.The result showed that price satisfaction, price confidence, price quality ratio, price fairness, and price transparency have significant effect toward price satisfaction. The relative price variable didn’t have significant effect toward price satisfaction. For the price satisfaction toward word of mouth, also didn’t give significant result. Based on the measurement of price satisfaction, managers are able to identify the drivers of price satisfaction, their satisfaction and relative importance in different market segments and, consequently they are able to take the right measures to increase customer satisfaction and word of mouth.Keywords : Price satisfaction, word of mouth, car workshop.